Comparative quantification of health risks global and regional burden of disease attributable to selected major risk factors - Ezzati, Majid; Lopez, Alan D.; Rodgers, Anthony; Murray, Christopher J.L.; World Health Organization (World Health Organization, 2004)
This book provides comprehensive assessment of the scientific evidence on prevalence and the resulting health effects of a range of exposures that are known to be hazardous to human health, including childhood and maternal undernutrition, nutritional and physiological risk factors for adult health, addictive substances, sexual and reproductive health risks, and risks in the physical environments of households and communities, as well as among workers. This book is the culmination of over four years of scientific enquiry and data collection, known as the comparative risk assessment (CRA) project, which involved over 100 scientists applying a common analytical framework and methods to ensure greater consistency and comparability in using and evaluating scientific evidence across risks.
Title from disc label.